2022
DOI: 10.1055/s-0042-1753042
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Palladium-Catalyzed Carbonylative Cyclization of Aryl Iodides and 2-Hydroxyacetophenones towards Flavones

Abstract: A highly efficient heterogeneous palladium-catalyzed carbonylative cyclization of aryl iodides and 2-hydroxyacetophenones is developed. The reaction proceeds efficiently in DMSO at 120 °C under 3 bar of carbon monoxide by using 2 mol% of an MCM-41-immobilized bidentate phosphine palladium complex [MCM-41-2P-Pd(OAc)2] as the catalyst and 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) as the base, providing a general, efficient and practical approach for the assembly of a wide variety of flavones in mostly good to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…The relationship between the percentage inhibition at diverse concentrations was plotted after taking into account the IC 50 rate in comparison with the inhibitory curve. It was determined in a previous report that synthetic 4‐alkoxyphenyl‐nitrothiophene hybrids would have strong antioxidant activity because molecules with arenesl moieties in their construction permitted radical trapping [21]. Table 2 shows that the synthesized alkoxyphenyl‐nitrothiophene hybrids have enough antioxidant activity.…”
Section: Resultsmentioning
confidence: 98%
“…The relationship between the percentage inhibition at diverse concentrations was plotted after taking into account the IC 50 rate in comparison with the inhibitory curve. It was determined in a previous report that synthetic 4‐alkoxyphenyl‐nitrothiophene hybrids would have strong antioxidant activity because molecules with arenesl moieties in their construction permitted radical trapping [21]. Table 2 shows that the synthesized alkoxyphenyl‐nitrothiophene hybrids have enough antioxidant activity.…”
Section: Resultsmentioning
confidence: 98%
“…A study of the literature suggested that synthetic benzothiazolyl‐chromenone‐based fluorophore hybrids would have substantial antioxidant effectiveness because hybrids with multiple aryl moieties in their backbone allow radical's scavenging. [23]. Table 2 shows that the synthesized benzothiazolyl‐chromenone‐based fluorophore hybrids had adequate antioxidant effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…A study of the literature suggested that synthetic benzothiazolyl-chromenone-based fluorophore hybrids would have substantial antioxidant effectiveness because hybrids with multiple aryl moieties in their backbone allow radical's scavenging. [23]. 1.…”
Section: Antioxidant Efficacymentioning
confidence: 99%
“…After taking into account the IC 50 values verse the inhibitory curve, the graph between inhibition per cent and various concentrations was plotted. Considering that compounds with diaryl moieties in their skeleton allow radical inhibition, it was estimated from a review of the literature that synthesized substituted iodobiphenyl analogues would have significant antioxidant activities[35]. Sufficient antioxidant activity of the generated alkyloxy-substituted iodobiphenyl analogues is recorded inTable 2.…”
mentioning
confidence: 99%